Efeito do tempo de armazenamento, corte e fungicida sobre a germinação das sementes e sobre o crescimento de plântulas de mangueira (Mangifera indica L.) - R Chauran, Omar; Manica, Ivo; V R Pinheiro, Rubens; R Condé, Alcides; R P Chaves, José (Revista Ceres, 2025)
The effects storage period, removal or cutting of the endocarp and tungicide application on germination mango (Mangifera indica L.) seeds were studied in a greenhouse experiment at the Federal University of Viçosa, Minas Gerais, Brazil. Storage periods were 0, 7, 14, 21 and 28 days. Cutting treatments consisted of leaving the endocarp intact, removing it completely, making one apical cut and making both apical and basal cuts. The fungicide tested was Neantin (methoxyl mercuric chloride).